Investigation of tracking phenomenon in cable joints as 3D with finite element method - İSPİRLİ, MEHMET MURAT (SPRINGER, 2018)
Underground cables are manufactured finite length in terms of commercial use. As the underground cables are produced for commercial use, the length is often insufficient for transmission and distribution lines. Therefore, the cables are added together to provide the desired length by using joints. At the joint points, insulators such as cable terminal cap and resin are used. In this study, surface tracking process of polyurethane resin, which is a filling material used in underground energy transmission and distribution systems, is investigated using finite elements method. A finite elements model is created based on IEC 60112 test standard. The developed model was used to investigate the electric potential and electric field distribution between the electrodes for different positions of the solution droplet, which is needed to use in the test, on the polymer sample surface.
Keywords: Comparative tracking index (CTI); Finite element analysis (FEA); 3D electric field computation; SILICONE-RUBBER; BREAKDOWN; FAILURE